Characteristics of educator B.Odsuren’s teaching methods (Mongolian Journal of Arts and Culture, 2024)
This article aims to elucidate the fundamentals of B.Odsuren’s teaching methodology, the pioneer of classroom training in Mongolian khuumii. It delves into the distinctive features of his teaching approach and the guiding principles it entails. To achieve this objective, an emphasis is placed on tracing B. Odsuren’s journey in learning khuumii and his subsequent experience in imparting this skill to others. The article highlights that while the structured training plans and curricula of formal khuumii education adhere to a standardized framework, the traditional approach of “Apprenticeship” remains prevalent in the teaching methodology of experienced practitioners. This method emphasizes the transmission of the traditional folk art from teacher to student, ensuring the preservation and continuation of cultural heritage. In fact, the teacher’s teaching method is a part of the “regulated school” in music education. Baatarin Odsuren, a well-known teacher of khuumii art, reciter and storyteller, who has made a special contribution to the formation of a training system with its own components in modern khuumii art, and who has accumulated rich experience for more than 30 years of his life in this field, is undoubtedly. This article examines how a special teaching pattern, named after the teacher Odsuren been formed, how his life experience was incorporated into his pedagogical concepts and teaching methods, and how he became a standard in the teaching methods of his future students, was revealed through the teaching process, oral sources, and interviews. The data and information relevant to the study were collected through unstructured observation and discussion with the educator B.Odsuren and his students during the course of the “Traditional folk art” program of the Mongolian National University of Arts and Culture. The research was conducted using a qualitative method based on the content analysis method.Сурган хүмүүжүүлэгч Б.Одсүрэнгийн хөөмий заах арга барилын онцлогХураангуй: Энэхүү өгүүллийн зорилго монгол хөөмийн танхимын сургалтын үндэслэгч, багш Б.Одсүрэнгийн сурган хүмүүжүүлэх арга ухааныг тодруулах замаар түүний заах арга, түүнд баримтлах зарчмуудыг авч үзэхэд чиглэгдэнэ. Үүний тул Б.Одсүрэнгийн хөөмийд суралцсан болон бусдад зааж сургасан туршлагыг онцлохыг зорив. Хэдийгээр дээд боловсролтой хөөмийч бэлтгэн төгсгөхөд сургалтын хөтөлбөрийн дагуу үндсэн чиглэлийг баримталж байгаа ч үндэсний язгуур урлагийг бусдад өвлүүлж байгаа талаараа багшийн заах арга барилд “шавь сургалт”-ын уламжлалт хэлбэр илүүтэй зонхилж байгааг тус өгүүллээр дамжуулан мэдээлэв. Угтаа багшийн заах арга бол хөөмийн сургалт дахь “дэг сургууль”-ийн нэгэн бүрдэл болох юм. Монгол хөөмийн урлагт өөрийн гэсэн бүрдэл хэсгүүдтэй орчин цагийн дэг сургууль бүрэлдэн тогтоход онцгой хувь нэмэр оруулсан, амьдралынхаа 30 гаруй жилийг энэ салбарт зориулж, арвин туршлага хуримтлуулсан хүн бол яахын аргагүй хөөмийн урлагийн нэрт сурган хүмүүжүүлэгч, ерөөлч магтаалч, туульч Баатарын Одсүрэн юм. Түүний сурган хүмүүжүүлэх үзэл баримтлал, заах арга барилд туулж өнгөрүүлсэн амьдралын туршлага нь хэрхэн шингэсэн, цаашлаад хойч үеийн шавь нарынх нь заах арга барилд хэрхэн жишиг болж, мөрдөгдөж байгааг хичээл сургалтын үйл явц болон аман сурвалж, ярилцлагаас тодруулж, Б.Одсүрэнгийн гэх заах арга барилын хэв загвар тогтсон байгааг энэ өгүүллээр авч үзэв. Судалгаанд холбогдох өгөгдөл, мэдээллийг Монгол Улсын Соёл урлагийн их сургуулийн “Үндэсний язгуур урлаг” хөтөлбөрийн хөөмийлөх ур чадварын хичээлийн явцад зохион байгуулалтгүй ажиглалт хийж, сурган хүмүүжүүлэгч Б.Одсүрэн болон түүний шавь нартай ярилцах замаар цуглуулав. Тус судалгааг агуулгын шинжилгээний аргад тулгуурлан чанарын аргаар хийсэн болно.Түлхүүр үгс: шавь сургалт, танхимын сургалт, дэг сургууль, хөөмийлөх ур чадвар